Immediate compared with delayed oxytocin after amniotomy labor induction in parous women a randomized controlled trial - Tan, P.C.; Soe, M.Z.; Sulaiman, S.; Omar, S.Z. (2013)
OBJECTIVE: To compare immediate with delayed (4 hours) oxytocin infusion after amniotomy on vaginal delivery within 12 hours and patient satisfaction with the birth process. METHODS: Parous women with favorable cervixes after amniotomy for labor induction were randomized to immediate titrated oxytocin or placebo intravenous infusion in a double-blind noninferiority trial. After 4 hours, study infusions were stopped, the women were assessed, and open-label oxytocin was started if required. Maternal satisfaction with the birth process was assessed with a 10-point visual numerical rating scale (lower score, greater satisfaction). RESULTS: Vaginal delivery rates at 12 hours were 91 of 96 (94.8) compared with 91 of 94 (96.8) (relative risk 0.98, 95 confidence interval CI 0.92-1.04, P=.72), and maternal satisfaction on a visual numerical rating scale (median interquartile range) was 3 3-4 compared with 3 3-5, P=.36 for immediate compared with delayed arm, respectively). Cesarean delivery, maternal fever, postpartum hemorrhage, uterine hyperactivity, and adverse neonatal outcome rates were similar between arms. The immediate oxytocin arm had a shorter amniotomy-to-delivery interval of 5.3 +/- 3.1 compared with 6.9 +/- 2.9 hours (P<001) and lower epidural analgesia rate of 2.9% compared with 9.9% (relative risk 0.3, 95% CI 0.1-1.0, P=.046), but fetal heart rate abnormalities on cardiotocogram were higher, 28.6% compared with 16.8% (relative risk 1.7 95% CI 1.0-2.9, P=.048). In the delayed arm, oxytocin infusion was avoided by 35.6%. CONCLUSIONS: Immediate or delayed oxytocin infusions are reasonable options after amniotomy for labor induction in parous women with favorable cervixes. The choice should take into account local resources and the woman's wish.